Effect of the antiparasitic drug "Closantel" on fetal development and some biochemical parameters in rabbits - Youssef, Amany E. (2002)
The teratogenic effect of closantel subcutaneously injected in closes of 5 and 10 mg / kg. b. wt. dur- ing the period or organogenesis was studied in rabbits. Moreover its effect on some serum bio- chemical constituents was studied. Closantel de- creased significantly fetal body weight and per- centage of living foetuses. Dilatation of lateral ventricles of the brain, pericarditis, intrathoracic haemorrhage, hypoplasia of the lung, dilatation of renal pelvis. spinal bifida incomplete ossification of skull bones and absence of some sternbrae and phalanges were reported. Closantel increased significantly the activities of Aspartate - aminotransferase (AST), Alanine aminotransferase (ALT) and Alkaline phosphatase (ALP). It also increased the concentration of ser- um total bilirubin, urea and creatinine but decreased the level of total protein.
Includes references.
1
Keywords: Rabbits -- Diseases; Antiparasitic agents; closantel